THE EFFECT OF LEVERAGE, CAPITAL INTENSITY AND LIQUIDITY ON TAX AVOIDANCE - Clara Aurelia Effendi; Henryanto Wijaya (Graduate Program of Universitas Tarumanagara, 2026)
This study aims to analyze the influence of leverage, capital intensity, and liquidity on tax avoidance among consumer non-cyclical companies listed continuously on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative approach was used, relying on secondary data from companies’ annual financial reports. The sample was selected using a purposive sampling method, resulting in 62 companies with a total of 186 observations over three years. Data were analyzed using multiple linear regression with the help of EViews 12 and Microsoft Excel. The results show that leverage, capital intensity, and liquidity each have no significant effect on tax avoidance. This indicates that a firm’s debt structure, level of investment in fixed assets, and liquidity capacity do not significantly determine its tax avoidance behavior. Consequently, it can be concluded that tax avoidance is likely driven by other factors beyond financial characteristics, and future studies are encouraged to include additional variables for a more comprehensive understanding.